Pengaruh Pelatihan dan Kompetensi terhadap Kinerja Karyawan PT WIKA Pada Proyek Besar Tol IKN Kalimantan Timur - Dian Iskandar; Mulfi Sandi Yuda; Yoki Muchsam; Mochamad Afrizal Maulana (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2025)
Improving employee performance in large-scale construction projects such as the construction of the East Kalimantan IKN Toll Road is an important factor in ensuring work quality, timeliness, and project implementation efficiency. The complexity of construction work requires companies to have trained and competent human resources to be able to carry out tasks effectively. Therefore, this study aims to analyze the effect of training and competence on employee performance at PT WIKA in large projects such as the East Kalimantan IKN Toll Road. This study uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents who are project employees. Data analysis techniques used multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that training and competency have a positive and significant effect on employee performance, both partially and simultaneously. The Adjusted R Square value of 0.716 indicates that 71.6% of the variation in employee performance can be explained by these two variables.